2022
DOI: 10.1111/chso.12667
|View full text |Cite
|
Sign up to set email alerts
|

Bear in a Window: Australian children's perspectives on lockdown and experiences of the COVID‐19 pandemic

Abstract: This paper examines the reflections of a cohort of Australian children who lived through the 2020–21 COVID‐19 pandemic and experienced being in ‘lockdown’; a state of largely being confined to the home for long periods daily. We report how children reflect on their experiences and illustrate how reflections draw on similar topics focused on localised child concerns regarding health, education, family, digital engagement, mealtimes and food. Further, we argue for the importance of including children's own voice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…They found that despite the challenges and lost opportunities, “children emerged as competent social agents and responsible citizens” [16 p. 144]. Likewise, Kelly and Diskin-Holdaway [17], in a study of experiences of the pandemic in 18 children aged 3–12 years old in Australia, found that children were worried about health and family and were disappointed about missed opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…They found that despite the challenges and lost opportunities, “children emerged as competent social agents and responsible citizens” [16 p. 144]. Likewise, Kelly and Diskin-Holdaway [17], in a study of experiences of the pandemic in 18 children aged 3–12 years old in Australia, found that children were worried about health and family and were disappointed about missed opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with direct participation of children in matters that concern them as laid down in the Convention of the Rights of the Child [22]. Instead of collecting parents' and teachers' narratives about children's experiences (which, in our usage of the terms, would be an etic approach), studies increasingly focus on asking children about their own experiences [23][24][25]. Children's own (emic) experiences have been termed a children's perspective, parents' or teachers' (etic) perspectives of children a child perspective in sociological studies on children [26,27].…”
Section: Emic and Etic Perspectives Applied To Studies With Childrenmentioning
confidence: 99%
“…In Kelly and Diskin‐Holdaway's (2023) study, an online experimental platform was developed to prompt children to share their lockdown experiences with a smiling teddy bear on screen, which was creatively evolved from a community activity called ‘bear in window’ during lockdowns in Australia. Kelly and Diskin‐Holdaway (2023) discuss the strengths and limitations of this method, which informs future studies adopting digital methods in research with children. In addition to discourse analysis, the authors also explore the linguistic patterns in children's responses, which provides innovative new insights into how children form and express their voices.…”
Section: To Empower Children and Young People As Co‐constructors Of K...mentioning
confidence: 99%